2009
DOI: 10.1007/s00468-009-0343-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and structural features of secretory canals in root and shoot wood of Copaifera langsdorffii Desf. (Leguminosae–Caesalpinioideae)

Abstract: Copaifera langsdorffii Desf., popularly known as copaíba, is an oleoresin-producing tree has been overexploited in Brazil by the pharmaceutical, cosmetic and varnish industries. Despite the long history of the use of this species, the structural knowledge on the resin-producing sites remains inadequate and is limited to the trunk. The aim of this study was to describe the origin, structure and developmental features of secretory spaces present in shoot and root wood of C. langsdorffii, based on the usual techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Turner (1999) had previously drawn attention to the misinterpretation of artifacts (result of the employment of some fixatives) as cell lyses and recommended caution in the study of lumen origin. The content found in the lumen of leaf secretory cavities of C. trapezifolia is similar to that found in the stem secretory canals, being oily and resinous, confirming previous studies of other Copaifera species (Veiga and Pinto 2002;Rodrigues and Machado 2009;Rodrigues et al 2011). The phenolic compounds found in the cavity/canal epithelial cells of C. trapezifolia (present work) and C. langsdorffii (Rodrigues et al 2011) deserve future studies of biological activity, since these compounds largely found in legumes have presented medicinal properties (Santos and Mello 2007).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Turner (1999) had previously drawn attention to the misinterpretation of artifacts (result of the employment of some fixatives) as cell lyses and recommended caution in the study of lumen origin. The content found in the lumen of leaf secretory cavities of C. trapezifolia is similar to that found in the stem secretory canals, being oily and resinous, confirming previous studies of other Copaifera species (Veiga and Pinto 2002;Rodrigues and Machado 2009;Rodrigues et al 2011). The phenolic compounds found in the cavity/canal epithelial cells of C. trapezifolia (present work) and C. langsdorffii (Rodrigues et al 2011) deserve future studies of biological activity, since these compounds largely found in legumes have presented medicinal properties (Santos and Mello 2007).…”
Section: Discussionsupporting
confidence: 89%
“…However, cases of lysogenesis have been described in species of Hymenaea (Paiva and Machado 2007) and Pterodon (Paiva et al 2008). An overlap of schizogenesis and lysogenesis was reported in C. langsdorffii by Rodrigues and Machado (2009) and Rodrigues et al (2011) after ultrastructural and immunohistochemical (TUNEL) studies, which indicated the programmed cell death of epithelial cells. Turner (1999) had previously drawn attention to the misinterpretation of artifacts (result of the employment of some fixatives) as cell lyses and recommended caution in the study of lumen origin.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Secretory cavities and canals are common in many members of Leguminosae and can occur in vegetative (Lersten and Curtis 1986;Turner 1986;Teixeira et al 2000;Teixeira and Gabrielli 2000;Marcati et al 2001;Paiva and Machado 2007;Rodrigues and Machado 2009;Teixeira and Rocha 2009;Rodrigues et al 2011aRodrigues et al , 2011bMilani et al 2012) or reproductive organs (Paiva et al 2008;Teixeira and Rocha 2009). These structures in legumes have taxonomic (Turner 1986;Lersten and Curtis 1996;Teixeira et al 2000;Gabrielli 2000, 2006), ecological (Langenheim et al 1982;Arrhenius and Langenheim 1983;Langenheim 2003), and economic (Coelho et al 2001;Langenheim 2003;Plowden 2003) aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Most literature deals with the development of diverse secretory reservoirs of single species (e.g., Bennici and Tani, 2004) or concentrates on conifers and legumes, as their gumresins or resins are of commercial importance (Hong Wu and Zheng-hai Hu, 1997;Rodrigues and Machado, 2009;Bollschweiler et al, 2008 and others). Previous literature on the Cardueae deals mainly with the occurrence of secretory ducts or cavities on aerial organs, especially those of leaves and shoots, and the transition between root and shoot (Col, 1903(Col, , 1904.…”
Section: Introductionmentioning
confidence: 99%